1757. Using the Desirability of Outcome Ranking for Management of Antimicrobial Therapy (DOOR-MAT) to Assess Antibiotic Therapy Guided by Rapid Molecular Diagnostics (RMD) in Bloodstream Infection (BSI) Caused by Escherichia coli and Klebsiella pneumoniae. (26th November 2018) - Wilson, Brigid; Viau, Roberto; Perez, Federico; Jiang, Yunyun; Fowler, Vance G; Chambers, Henry F; Kreiswirth, Barry N; Bonomo, Robert A; Evans, Scott R; ,
Abstract: Background: In the setting of Escherichia coli and Klebsiella pneumoniae BSI, empiric antibiotic therapy is determined by clinical judgement and Gram stain (GS) of the positive blood culture bottle up to 2 days before antibiotic susceptibility test (AST) results become available. Within hours of GS, RMD can detect E. coli and K. pneumoniae and predict the pattern of susceptibility to β-lactams (BL) of differing spectrum. In this study, our objective was to compare "real-life" empiric therapy for E. coli and K. pneumoniae BSI administered between GS and AST results with simulated RMD-guided therapy. Methods: We identified a subset of patients hospitalized within VHA between 2006 and 2015 who had a blood culture positive for E. coli or K. pneumoniae, and received empiric BLs between GS and AST Results. We further restricted the cohort to those with observed or implied AST results for 4 representative BLs: cefazolin, ceftriaxone, piperacillin–tazobactam, and imipenem. We extracted BL resistance patterns and, based on previously analyzed RMD performance on 195 E. coli and K. pneumoniae, we simulated RMD results for our cohort by resampling RMD results stratified by resistance pattern at the observed frequencies of resistance patterns in our clinical isolates. We simulated therapy guided by RMDs and compared with the observed empiric BLs using a DOOR-MAT score (Figure 1). Results: A total of 36, 531 BSI cases were identified. Of these, 9, 981 E. coli and 4, 545 K. pneumoniae met our inclusion criteria (Figure 2). Among these, susceptibility to all BLs occurred in 88% of cases; resistance to all BLs occurred in <0.5%. The isolates previously analyzed using RMD included more resistant phenotypes (Figure 3). Empiric BLs were active in 98% of BSIs, with a mean DOOR-MAT score of 66.1 and 59% of cases classified as "moderate overtreatment." Simulated RMD-guided BL therapy would be active in 95% of cases with a mean DOOR-MAT score of 91.4 (95% CI, 91.2–91.7), and 7% of cases would be classified as overtreatment. Conclusion: In a large cohort of BSI patients where rates of BL resistance were low, we observed that empiric BL therapy, although highly effective, is of broader spectrum than necessary. RMD-guided therapy has the potential to reduce overtreatment without compromising effective therapy. DOOR-MAT provides a flexible framework for measuring appropriateness of therapy for BSI. Disclosures: All authors: No reported disclosures.